Analisis Piutang Usaha Pada PT. Pelabuhan Indonesia (Persero) Regional 1 Cabang Kuala Tanjung - Nadia Anzani; Kusmilawaty Kusmilawaty (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to analyze the receivables management system at PT. Pelabuhan Indonesia (Persero) Regional 1 Kuala Tanjung Branch is located on Jalan Pelabuhan No. 1 Kuala Tanjung, Sei Suka District, Batu Bara Regency. The type of data collected is qualitative data with descriptive methods. Data collection techniques in this research are observation, interviews and documentation. The source of the data obtained is secondary data in the form of documents or historical reports that have been compiled in an archive. This research uses the analytical method used, namely Analysis: The average collection period has not passed 90 days so it is still effective, the Receivable Turn Over (RTO) has not passed 15 times the trade receivable turnover so it is still in good condition, and the average age If the accounts receivable/Avarage Collection Period (ACP) is less than 8 days old, the trade receivables are still effective. The results of this research show that PT. Pelabuhan Indonesia (Persero) Regional 1 Kuala Tanjung Branch, management of the company's trade receivables is still effective.